2018
DOI: 10.3389/fonc.2018.00090
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Reprogramming During Multidrug Resistance in Leukemias

Abstract: Cancer outcome has improved since introduction of target therapy. However, treatment success is still impaired by the same drug resistance mechanism of classical chemotherapy, known as multidrug resistance (MDR) phenotype. This phenotype promotes resistance to drugs with different structures and mechanism of action. Recent reports have shown that resistance acquisition is coupled to metabolic reprogramming. High-gene expression, increase of active transport, and conservation of redox status are one of the few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…With the increasing research understanding on the resistance of chemo- and radiotherapy, the researchers have pointed out that cancer stem cells, tumor microenvironment, autophagy, and exosomes are all closely related to tumor chemo- and radio-resistance. In fact, recent reports have shown that chemo- and radio-resistance acquisition is coupled to deregulate glucose metabolism and glycolysis [35]. Signaling pathways related to chemo-radiotherapy resistance are abnormally activated or inactivated during metabolic stress, such as Wnt, PI3K/AKT, Notch, NF-κB, MAPK [3641].…”
Section: Main Textmentioning
confidence: 99%
“…With the increasing research understanding on the resistance of chemo- and radiotherapy, the researchers have pointed out that cancer stem cells, tumor microenvironment, autophagy, and exosomes are all closely related to tumor chemo- and radio-resistance. In fact, recent reports have shown that chemo- and radio-resistance acquisition is coupled to deregulate glucose metabolism and glycolysis [35]. Signaling pathways related to chemo-radiotherapy resistance are abnormally activated or inactivated during metabolic stress, such as Wnt, PI3K/AKT, Notch, NF-κB, MAPK [3641].…”
Section: Main Textmentioning
confidence: 99%
“…These precursors are required for rapidly proliferating tumor cells [9] . Second, the rate of glycolysis is much faster than that of OXPHOS [10 , 11] . This may be particularly advantageous in situations where a sudden increase of energy demand occurs, like in tumor cells undergoing an epithelial-mesenchymal transition (EMT) [12 , 13] .…”
Section: Introductionmentioning
confidence: 99%
“…These connections are especially interesting given the rapidly growing evidence that RB1 is needed for cells to maintain a normal metabolic balance, and that the loss of RB1 leads to reprogramming of specific pathways [70][71][72] . Metabolic adaptations are thought to enhance the ability of cancer cells to sustain the metabolic intermediates for cell survival during multidrug resistance 73,74 . Our results outline a clinically feasible scenario to use RB1 as a biomarker to stratify the TNBC patients for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%